استخدام الخيوط المعدنية في تطوير إنتاج اقمشة المفروشات للحصول على منتج تنافسي - حلاوة، أسامة عز الدين علي; عبدالحميد، جمال محمد (جامعة المنصورة - كلية التربية النوعية, 2012)
اعتمدت العينات المنتجة بالبحث على إظهار قدرة المصمم في توزيع المساحات اللونية داخل التصميم وقدرته على استخدام خامة الخيوط المعدنية كلحمات وتوزيع ظهورها داخل القماش المنتج وذلك لتطوير عملية إنتاج أقمشة المفروشات والوصول إلى منتج يتميز باحتوائه على فكرة جديدة مبتكرة ومتميزة في استخدام الخيوط المعدنية كلحمات وكيفية اختلاف أسلوب توزيعها داخل التصميم للمنتج النسيجي والتباين في ظهور الخيوط المعدنية بمساحات النقش أو بالأرضية أو على حدود النقش والزخرفة فقط لإعطاء مظهر جمالي جديد ومبتكر للأقمشة المنتجة بالبحث ويناسب في نفس الوقت الأداء الوظيفي لهذه الأقمشة واستخداماتها كأقمشة مفروشات أو ستائر. وإلى جانب التغيير في مساحات الظهور الخاصة بالخيوط المعدنية داخل التصميم قد تم إنتاج عينات البحث باستخدام مواصفتين مختلفين لخيوط السداء حيث أستخدم خيوط السداء ذات لون واحد فقط على ماكينة بالإضافة إلى استخدام خيوط السداء من لونين وبترتيب (1: 1) على ماكينة أخرى وذلك للتعرف على إمكانية وقدرات المصمم الابتكارية في التحكم بمساحات ظهور الخيوط المعدنية وتوزيعها بالتصميم والعينات المنتجة بالبحث سواء كان السداء بلون واحد أو بلونين. The produced samples of the research depended on showing up the designer ability at controlling the distribution of the colour areas in the design and his ability to use the metallic yams as weft yams and distributing their appearance on the textile design so as to develop the upholstery fabrics production and to reach a product specialized by having a new invented idea and unique in using the metallic yams as weft yams and have the way of differing the method of their distribution in the design of the textile product and varying the appearance of the metallic yams on the ornamentation or the ground or as outline to the ornamentation only in the design to give a new beautiful appearance and innovated to the fabrics produced in this research and suits at the same time their function performance and their usage as upholstery or curtains. Beside variation the appearing areas of the metallic yams in the design we produced the research samples by two different specifications for the warp where we used one colour for the first warp and two colours with sequent (1:1) for the second warp on the other machine and that was done to know the creative abilities of the designer to control the appearing areas of the metallic yams and distributing it in the design and the produced samples in the research though the warp is one or two colours.
Keywords: أقمشة الستائر -- المنافسة الاقتصادية -- الخيوط المعدنية -- أقمشة المفروشات -- الزخارف -- تصميم المنسوجات